WORD-BUILDING AND STRUCTURAL FEATURES OF ENGLISH AND UZBEK DIPLOMATIC TERMINOLOGY - Xonto‘rayeva , Yulduz Kenjaboy qizi; Xolibekova , Omongul Kenjaboyevna (Innovative Development in Educational Activities, 2024)
This paper delves into the intricacies of diplomatic terminology in English and Uzbek, with a primary focus on the diverse word-building processes and structural frameworks employed in both languages. It meticulously examines how affixes and compound words are utilized to construct specialized vocabulary for diplomacy. Drawing upon linguistic research and insights from scholars like Cornelia Ilie and Marianne Mason, the study underscores the significance of understanding these linguistic mechanisms for effective communication and cultural competence in international relations. Specifically, it accentuates the relevance of such research for nations like Uzbekistan. Through a comprehensive comparative analysis, the paper aims to shed light on the nuanced structures of diplomatic terms, enhancing interpretation, negotiation, and translation within diplomatic contexts.